The role of self-education in distance learning (International relations and international law Journal, 2018)
In the modern fast-changing world, the education system has to meet numerous challenges of time.New approaches to modernization of the Kazakhstani education system, introduction of the new generationstandards determine priority goals and objectives whose solution demands high level of educationquality. Today the society is interested in graduates with developed cognitive needs aimed at self-educationand self-development, being able to operate the knowledge got, to orientate in the modern informationspace. Self-education of the student’s personality, as an independent direction of pedagogicalresearch, emerged in the science comparatively recently. The term ‘self-education’ is met frequently instudies and scientific pedagogical publications, but a uniform approach to the studied problem has notbeen designated in the science yet. Taking into account new position of students as subjects of education,higher education institutions are rebuilding the status of their purposefully organized independentwork, perfecting its normative and legal and information bases. One of the directions of its developmentis the distant form of education, based upon self-education. We understand self-education of studentsas activity aimed at achievement of certain educational goals: satisfaction of professional requests, gainingnew knowledge, continuous professional education, owing to which knowledge is actualized andexpanded. The most important in the structure of self-education of students is a motivation component,which includes: professional interest, strive to self-perfecting. In the process of distant education, certainrelations of educational character arise, which are the very catalyzer of self-development processes.Self-education becomes an individual and social value, provides mobility and wide opportunities to theyouth in the educational sphere. Introduction of distant education as a means of realization of individualeducational trajectories of students is an important tendency of development of the Kazakhstani educationalsystem. The article gives arguments in favor of the necessity of formation of skills and abilities ofself-education for efficient realization of distant education.Key words: self-education, distant education, educational process, pedagogical support, independentwork.